The Ecological Crisis and Worldview: An Analytical Study of Secular and Islamic Perspective - Harda Armayanto; Adib Fattah Suntoro; Ulfatun Wahidatun Nisa; Amir Sahidin; Luthfi Muhyiddin (Tasfiyah: Jurnal Pemikiran Islam, 2026)
This article analyzes the relationship between ecological crisis and the construction of the human worldview, explaining how certain paradigms contribute to environmental degradation. Conceptually, ecological crisis and worldview  distinct entities; however, they are closely interconnected, as worldview functions as the primary driving force in shaping both social and moral continuity and transformation. Accordingly, human perception of the world generates actions, including responses to global ecological problems; thus, errors in worldview lead to inappropriate actions toward nature. This study employs a qualitative method with a library research approach, drawing on a range of literature, both classical and contemporary, in both print and digital formats. The analysis is conducted through a conceptual exposition of worldview and ecological crisis, followed by an examination of their relationship. The findings indicate that the contemporary ecological crisis cannot be separated from the dominance of the Western secular worldview, which tends to position nature as an object of exploitation. As an alternative, this article proposes the Islamic worldview as a solution, which for more than 1,400 years has taught the principles of balance and responsibility toward nature. The concepts of iṣlāḥ (reform) and ifsād (corruption/destruction) serve as ethical foundations for establishing a harmonious relationship between humans and the environment. Furthermore, this study recommends that future research further develop and empirically examine the implementation of the Islamic paradigm as both a conceptual and practical approach to environmental preservation.